Primary tooth pulpectomy overfilling by different placement techniques: A systematic review and meta-analysis - Aminabadi, Naser Asl (J Dent Res Dent Clin Dent Prospects, 2020)
Background. This study was conducted to investigate root canal overfilling with different material placement techniques in primary teeth. Methods. A systematic search was undertaken by searching PubMed/MEDLINE and Scopus for English language peer-reviewed articles published until February 2018 that reported primary tooth pulpectomy overfilling. Two reviewers independently screened and identified studies in terms of the selection criteria and independently collected the data using a specially designed data extraction form. The overfilling rate was the primary summary measure. The weighted pooled overfilling rates were estimated by random-effects meta-analysis. Results. Twenty clinical and four in vitro studies met the eligibility criteria. In the clinical studies, the pooled overfilling rate for zinc oxide-eugenol (ZOE) was 23.3% with a lentulo spiral mounted on a handpiece, 22.7% with a hand-held lentulo spiral, and 17% with a plugger. The pooled overfilling rate for calcium hydroxide-based materials was 16.7% with a lentulo spiral mounted on a handpiece, 14.7% with a hand-held lentulo spiral, 19.6% with a syringe, and 25.7% with a plugger. In the in vitro studies, neither individual overfilling rates nor two-by-two comparisons were subjected to meta-analysis because of an inadequate number of studies. Conclusion. The lowest overfilling rate in the clinical studies was related to plugger and handheld lentulo spiral techniques for ZOE and calcium hydroxide-based materials, respectively